Covid-19:Relasi Sosial Siswa di Banten pada Pembelajaran Jarak Jauh (PJJ) - Dede Yusuf; Rizki Setiawan (Dimensia: Jurnal Kajian Sosiologi, 2021)
The impact of the Covid-19 pandemic on the education sector is the implementation of distance online learning. This weakens the educational system in a variety of ways, including the social sphere.Social activity that used to held in schools is not possible to do that leads to creating barriers to direct social processes among students. As a result, this research aims to explain how the social relationships of Banten local high school students in the distance learning/PJJ situation in the Covid-19 pandemic. This research using the survey method. The findings show that: The quantity of face to face interaction is uncommon and not voluntary.The indirect interaction through media and technology are intense and creating familiarity in indirect online interaction pattern.